Benefits of Motor Imagery for Human Space Flight: A Brief Review of Current Knowledge and Future Applications - Guillot, Aymeric; Debarnot, Ursula (Frontiers in Physiology, 2019)
Motor imagery (MI) is arguably one of the most remarkable capacities of the human mind. There is now strong experimental evidence that MI contributes to substantial improvements in motor learning and performance. The therapeutic benefits of MI in promoting motor recovery among patients with motor impairments have also been reported. Despite promising theoretical and experimental findings, the utility of MI in adapting to unusual conditions, such as weightlessness during space flight, has received far less attention. In this review, we consider how, why, where, and when MI might be used by astronauts, and further evaluate the optimum MI content. Practically, we suggest that MI might be performed before, during, and after exposure to microgravity, respectively, to prepare for the rapid changes in gravitational forces after launch and to reduce the adverse effects of weightlessness exposition. Moreover, MI has potential role in facilitating re-adaptation when returning to Earth after long exposure to microgravity. Suggestions for further research include a focus on the multi-sensory aspects of MI, the requirement to use temporal characteristics as a measurement tool, and to account for the knowledge-base or metacognitive processes underlying optimal MI implementation.